Innovative Assessment That Combines Collaborative and Self-Directed Learning With Integration and Application of Knowledge: Teamwork Group Projects - Chinthaka Balasooriya; Asela Olupeliyawa; Maha Pervaz Iqbal (Association of American Medical Colleges, 2016)
Abstract Introduction There is a worldwide focus on the early development of collaborative skills in medical students as reflected in the design of the medicine program at the University of New South Wales, Australia. Integral to the success of student-centered curricula, is early development of students' self-directed and collaborative learning skills. The purpose of this innovative assessment is to develop and assess students' skills in self-directed and collaborative learning while they concurrently engage with stage-appropriate content knowledge. Methods The educational design of the group projects allows junior medical students to work collaboratively to develop a deep understanding of the concepts and principles of a clinical scenario. Students are required to integrate and apply knowledge from different disciplines and share their learning with a wider peer group through appropriate peer teaching strategies. Two variants of these group projects are described in this resource, and generic versions of student and assessor instructions are included as Appendices A and B. Results Feedback on the projects collected over the last 7 years has been positive. Students begin to see the relevance and benefits of learning together and appreciate the impact this has on the quality of their learning. They also begin to appreciate the relevance of collaborative skills to their future practice as doctors. Discussion The group projects are based on well-established educational principles, and the templates provided in the appendices can be adapted by other medical educators.